Molecular Characterization and Antifungal Susceptibility of Clinical Fusarium Species From Brazil - Herkert, Patricia F.; Al-Hatmi, Abdullah M. S.; de Oliveira Salvador, Gabriel L.; Muro, Marisol D.; Pinheiro, Rosângela L.; Nucci, Márcio; Queiroz-Telles, Flávio; de Hoog, G. Sybren; Meis, Jacques F. (Frontiers in Microbiology, 2019)
Fusarium is widely distributed in the environment and is involved with plant and animal diseases. In humans, several species and species complexes (SC) are related to fusariosis, i.e. F. solani SC, F. oxysporum SC, F. fujikuroi SC, F. dimerum, F. chlamydosporum, F. incarnatum-equiseti and F. sporotrichoides. We aimed to investigate the susceptibility of Fusarium clinical isolates to antifungals and azole fungicides and identify the species. Forty-three clinical Fusarium isolates were identified by sequencing translation elongation factor 1-alpha (TEF1α) gene. Antifungal susceptibility testing was performed to the antifungals amphotericin B, itraconazole, voriconazole, posaconazole and isavuconazole, and the azole fungicides difeconazole, tebuconazole and propiconazole. The isolates were recovered from patients with median age of 36 years (range 2–78 years) of which 21 were female. Disseminated fusariosis was the most frequent clinical form (n=16, 37.2%) and acute lymphoblastic leukemia (n=7; 16.3%) was the most commonly underlying condition. A few species described in Fusarium solani SC have recently been renamed in the genus Neocosmospora, but consistent naming is yet not possible. Fusarium keratoplasticum FSSC 2, (n=12) was the prevalent species, followed by F. petroliphilum FSSC 1 (n=10), N. gamsii FSSC 7 (n=5), N. suttoniana FSSC 20 (n=3), F. solani sensu stricto FSSC 5 (n=2), Fusarium sp. FSSC 25 (n=2), Fusarium sp. FSSC 35 (n=1), Fusarium sp. FSSC18 (n=1), F. falciforme FSSC 3+4 (n=1), F. pseudensiforme (n=1), and F. solani f. xanthoxyli (n=1). Amphotericin B had activity against most isolates although MICs ranged from 0.5–32 µg mL-1. Fusarium keratoplasticum showed high MIC values (8–>32 µg mL-1) for itraconazole, voriconazole, posaconazole and isavuconazole. Among agricultural fungicides, difeconazole had the lowest activity against FSSC with MICs of >32 µg mL-1 for all isolates.